ASEAN integration: Malaysian business undergraduates’ readiness and perspectives on priority issues - Yen, Wan Chong (2015)
This study examined the perception of business undergraduates in a Malaysian university on their readiness to exploit regional opportunities following the establishment of the ASEAN Economic Community (AEC) by end 2015 as well as their perspectives on priory issues for ASEAN co-operation.It is found that while the majority of business undergraduates support the AEC and the freer flow of skilled professionals within the region, many students do not feel confident in their ability to compete with other ASEAN graduates. The business undergraduates’ readiness to compete with other ASEAN undergraduates were found to be positively correlated with their self-perception of their soft skill abilities. The students rated their ASEAN inter-cultural skills, comprising understanding of ASEAN languages, cultures and business etiquettes as their weakest soft skills.The study also revealed the “push and pull factors” of intra-ASEAN skilled labour mobility as perceived by business undergraduates. The findings of this research has important implications.In order to better equip graduates for a borderless job market in ASEAN as envisaged under the AEC, ASEAN universities should intensify efforts to develop multicultural skills among young graduates.Existing programs to develop soft skills may have overlooked the importance of multicultural skills, particularly intercultural ASEAN skills.